Polyelectrolyte Multilayers Promote Stent-Mediated Delivery of DNA to Vascular Tissue - Saurer, Eric M. (2013)
We report an approach to deliver DNA to vascular tissue in vivo using intravascular stents coated with degradable, DNA-containing polyelectrolyte multilayers (PEMs). Ionically-crosslinked multilayers ~120 nm thick were fabricated layer-by-layer on the surfaces of balloon-mounted stainless steel stents using plasmid DNA and a hydrolytically degradable poly(β-amino ester) (polymer 1). Characterization of stents coated using a fluorescently end-labeled analog of polymer 1 revealed film erosion to be uniform across the surfaces of the stents; differential stresses experienced upon balloon expansion did not lead to faster film erosion or dose dumping of DNA in areas near stent joints when stents were incubated in physiologically relevant media. The ability of film-coated stents to transfer DNA and transfect arterial tissue in vivo was then investigated in pigs and rabbits. Stents coated with films fabricated using fluorescently labeled DNA resulted in uniform transfer of DNA to sub-endothelial tissue in the arteries of pigs in patterns corresponding to the locations and geometries of stent struts. Stents coated with films fabricated using polymer 1 and plasmid DNA encoding EGFP resulted in expression of EGFP in the medial layers of stented tissue in both pigs and rabbits two days after implantation. The results of this study, combined with the modular and versatile nature of layer-by-layer assembly, provide a polymer-based platform that is well suited for fundamental studies of stent-mediated gene transfer. With further development, this approach could also prove useful for the design of non-viral, gene-based approaches to preventing complications that arise from the implantation of stents and other implantable interventional devices.